Supervisi pendidikan untuk penguatan sistem manajemen mutu sekolah - Muhammad Febri Mawardi; Rilo Pambudi Triantoro; Putri Medina Heru Arnafama; Sulistiyana Sulistiyana; Metroyadi Metroyadi (Curricula: Journal of Curriculum Development, 2026)
This study is motivated by the continued dominance of administrative and formalistic supervision practices that have not been optimally integrated with the school quality improvement cycle, resulting in a suboptimal contribution to education quality management. This study aims to analyze the role of educational supervision as a strategic instrument in strengthening school quality management in Indonesia. This study uses a Systematic Literature Review (SLR) approach with a PRISMA-based selection procedure and content analysis techniques, drawing on 36 national and international journal articles published in 2020–2025 relevant to educational supervision and school quality management. The synthesis results indicate that educational supervision plays a significant role in improving teachers' pedagogical and professional competencies through collaborative coaching, strengthening data-based decision-making, and integrating a continuous improvement cycle within the Total Quality Management framework. Effective supervision is constructive, evidence-based, and integrated into the school quality management system, thereby driving the quality system to build an adaptive and sustainable quality culture. These findings emphasize that supervision is not only a monitoring mechanism but also a strategic instrument for strengthening the school quality system as a whole.